The Influence of the Storytelling Method and Picture Media on the Speaking Skills of Fifth-Grade Students at SDN 5 Tanrutedong - Sitti Masdaniah; Nuraini Kasman; Aswadi (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
The purpose of this study is (1) To analyze the influence of storytelling on the speaking ability of fifth grade students at SD Negeri 5 Tanrutedong (2) To analyze the influence of image media on the speaking ability of fifth grade students at SD Negeri 5 Tanrutedong (3) To analyze the influence of storytelling and image media on speaking ability. This type of research is descriptive quantitative with a correlation approach. The population in this study was all fifth grade students at SD Negeri 5 Tanrutedong totaling 30 students. Data collection was carried out by means of questionnaires and documentation. Validity test using Bivariate Person correlation technique and reliability test using Cronbach alpha technique. Data analysis technique was carried out by descriptive analysis and inferential statistical analysis. The results of this study indicate that (1) There is a positive and significant influence of storytelling on the speaking ability of fifth grade students at SD Negeri 5 Tanrutedong with a significance value of 0.00<0.05 and a correlation value of 43.8% (2) There is a positive and significant influence of image media on the speaking ability of fifth grade students at SD Negeri 5 Tanrutedong with a significance value of 0.01<0.05 and a correlation value of 32.1% (3) There is a positive and significant influence of storytelling and image media on the speaking ability of fifth grade students at SD Negeri 5 Tanrutedong with a significance value of 0.00<0.05 and a correlation value of 60.9%.